RETRACTED: Quality evaluation of progeny of the sterlet Acipenser ruthenus (sterlet) obtained offspring - Ponomareva Elena; Firsova Angelina; Sorokina Marina; Kovalenko Matvey; Belaya Maria; Viet Thuy Nguyen (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001